Assessing the medium-term impact of a home-visiting programme on child maltreatment in England: protocol for a routine data linkage study. Issue 7 (13th July 2017) - Lugg-Widger, Fiona V; Cannings-John, Rebecca; Channon, Sue; Fitzsimmons, Deborah; Hood, Kerenza; Jones, Kerina H; Kemp, Alison; Kenkre, Joyce; Longo, Mirella; McEwan, Kirsten; Moody, Gwenllian; Owen-Jones, Eleri; et al.
Abstract : Introduction: Child maltreatment involves acts of omission (neglect) or commission (abuse) often by caregivers that results in potential or actual harm to a child. The Building Blocks trial (ISRCTN23019866 ) assessed the short-term impact of an intensive programme of antenatal and postnatal visiting by specially trained nurses to support young pregnant women in England. The Building Blocks: 2–6 Study will assess the medium-term impacts of the programme for mothers and children (n=1562), through the linkage of routinely collected data to the trial data, with a particular emphasis on the programme's impact on preventing child maltreatment. Methods and analysis: We have developed a bespoke model of data linkage whereby outcome data for the trial cohort will be retrieved by linked anonymous data abstraction from NHS Digital, Office for National Statistics and the Department for Education's National Pupil Database. Participants will be given reasonable opportunity to opt out of this study prior to data transfer. The information centres will match participants to the information held in their databases using standard identifiers and send extracts to a third-party safe haven. The study will have 80% power to detect a 4% difference (4%vs8%) for the binary primary outcome of child in need status (from birth to key stage 1) at a two-sided 5% alpha level by following up 602 children in each trial arm. Analysis will be by intention to treat using logistic multilevel modelling. A cost-and-consequences analysis will extend the time frame of the economic analysis from the original trial. Ethics and dissemination: The study protocol has been approved by the National Health Service Wales Research Ethics Committee and the Health Research Authority's Confidentiality Advisory Group. Methods of innovative study design and findings will be disseminated through peer-reviewed journals and conferences; results will be of interest to clinical and policy stakeholders in the UK. Trial registration number: ISRCTN23019866.